Bilateral tubercular abscess of breast in axillary tail in a 21 year old puerperal lady (Bangladesh Journal of Medical Science, 2011)
Tuberculosis is a very common disease in the Indian subcontinent. Though it can affect any system of the body, primary involvement of the breast is relatively rare even in India. Involvement of the axillary tail is even rarer. Bilateral involvement is also a rare phenomenon (3%). Moreover the disease is often overlooked and misdiagnosed as carcinoma or pyogenic abscess. Here we report a case of bilateral tubercular abscess of breast in the axillary tail in a 21 year old puerperal lady diagnosed by FNAC and AFB stains and further confirmed retrospectively by response to anti-tubercular drugs. Keywords: Tuberculosis; Breast. DOI: 10.3329/bjms.v10i1.7323 Bangladesh Journal of Medical Science Vol.10 No.1 Jan 2010 pp.60-63